Analysis of related deaths in patients with systemic sclerosis combined with renal failure in the United States from 1999 to 2020 - Rongxiu Huo; Yanting Yang; Chengcheng Wei; Danli Meng; Xiaocong Huo; Yang Yang; Bangqin Wang; Yijia Huang; Rongjun Huang; Jinying Lin; Xinxiang Huang (Scientific Reports)
Abstract To describe the number of deaths related to systemic sclerosis (SSc) having renal failure, the changing trend in ASMR, and causes of death using a multi-cause method. Annual death toll and ASMR data from 1999 to 2020 were obtained from the death database of the US CDC. All death certificates in the M34 (SSc) and N17-19 (renal failure) categories of the ICD-10 were selected as potential or related causes of death. The epidemiology was described, and number of deaths and ASMR trends were analyzed. NCI-Joinpoint Analysis was used to test the changing trends in different years. For 22 years, 39,496 and 5,163 deaths were related to SSc and SSc having renal failure, respectively. There were 1,139 males (22.1%) with SSc having renal failure and 4,024 females (77.9%) with 1:3.5 male-to-female ratio. The number of female deaths and the ASMR were higher than those of male deaths, and decreased. Most deaths occurred approximately > 75 years. The number of deaths in different age groups showed a downward trend. Acute renal function was dominant in patients with SSc. Although the mortality rate of SSc having renal failure was relatively low and decreasing, timely diagnosis and treatment are required to reduce the mortality rate.